A history of conversion to Islam in the United States. - Bowen, Patrick D. (Muslim Minorities, 2015)
A History of Conversion to Islam in the United States, Volume 1: White American Muslims before 1975 is the first in-depth study of the thousands of white Americans who embraced Islam between 1800 and 1975. Drawing from little-known archives, interviews, and rare books and periodicals, Patrick D. Bowen unravels the complex social and religious factors that led to the emergence of a wide variety of American Muslim and Sufi conversion movements. While some of the more prominent Muslim and Sufi converts-including Alexander Webb, Maryam Jameelah, and Samuel Lewis-have received attention in previous studies, White American Muslims before 1975 is the first book to highlight previously unknown but important figures, including Thomas M. Johnson, Louis Glick, Nadirah Osman, and T.B. Irving.